PENGARUH PEMBERIAN SMOOTHIES KOMBINASI BUAH DAN SAYUR TERHADAP PERUBAHAN KADAR GLUKOSA DARAH PUASA PADA WANITA DEWASA - Oktaviani, Endang; Jaelani, Mohammad; Supadi, J; Setiadi, Yuwono (JURNAL RISET GIZI, 2018)
Background : DM is a metabolic disease which is characteristic by hyperglycemia and not rarely DM patients dependent on drugs throughout their lives. Drug consumption provides certain side effects such as naunsea, vomiting, diarrhea, constipation, hypoglycemia and weight gain, therefore it is necessary to give alternative treatment in preventing the occurrence of DM with the consumption of fruits and vegetables.Objective : to determine the effect of smoothies combination of fruit and vegetable on alteration of fasting blood glucose level in adult women.Methode :The research type was True Experiment research and used Randomized Pretest Posttest Control Group Design. Independent T-test was used to analyze the differences of  blood glucose levels between the treatment group and the control group and ANOVA Repeated Measure Test was used to analyze  determine the relationship between smoothies combination of fruits and vegetables with controlled blood glucose levels and nutrient intake.Results :  There were no significant effect in fasting blood glucose levels (p=0.799) between treatment group and control group, while the energy, protein, fat, carbohydrate and fiber intake level were effected on fasting blood glucose levels but not significant (p 0.05).Conclusion : Consumption of smoothies combination of fruits and vegetables for 3 weeks can lower fasting blood glucose level in adult women by 5,33mg/dl (4,35%), althought statistically insignificant.